Geography and communication in indigenous territory: the culture of the naming ritual of the Boe (Bororo) people: Geography and communication in indigenous territory: the culture of the naming ritual of the Boe (Bororo) people (Élisée - Revista de Geografia da UEG, 2024)
: Geography is a science that values ​​and rescues traditional knowledge and, therefore, communication is necessary as a tool to access the territories of traditional peoples, as communication takes place in various forms, from writing to bodily representations. The territory is imbued with symbolism and characteristics of certain groups, it is the basis for recovering the cultural roots that define the specificities of the subjects who live there. The indigenous territory is one of the territories that brings in its material and immaterial manifestation the framework of struggles, customs, identity, conflicts, rituals and social relations that strengthen the village's collective bond. The indigenous territory of the Bororo people is full of traditions that value their customs and cultural practices, one of the rituals of great importance for the village is the naming ritual. The methodology of this work relies on fieldwork carried out during the geography and communication discipline, in addition to a bibliographical survey on the research topic. The results obtained show the importance of the territory of indigenous peoples for understanding various social and cultural aspects, as well as knowing part of the ancestry of the Brazilian people, in addition to understanding that communication takes place in various ways, mainly in the concrete reality of the territories.